Analytical modeling of a magnetically affected cantilever nanoplate-based mass detector. (January 2020) - Xu, Chenghui; Rong, Dalun; Tong, Zhenzhen; Zhou, Zhenhuan; Hu, Jingjing; Deng, Zichen
Abstract: A new model for a magnetically affected cantilever nanoplate-based mass sensor for detecting attached nanoparticles or long-chain molecule is developed and exact solutions are derived. A novel Hamiltonian-based method incorporating with nonlocal elastic theory is implemented to obtain the analytical solution of the mass sensor. The solutions are verified by comparing with published molecular mechanics and molecular dynamics simulation data and good agreements are recorded. The influences of the foundation modulus, nonlocal parameter, aspect ratio, magnetic field strength and thermal load on the frequency shift are examined. Numerical results show that the performance of the present detector is governed by the design parameters stated above; and applying an in-plane magnetic field is an efficient way to improve the sensitivity of cantilever mass detectors for a specific detector. The meaningful results will directly benefit the predesign and manufacture of such magnetically cantilever nanoplate-based nanosensor. Highlights: We propose a new magnetically affected cantilever nanoplate-based mass detector model. Exact solutions of the mass detector are obtained by a novel analytical method. Influences of the design parameters on the frequency shift are detailedly discussed. The mass detector can be used to identify the irregular long-chain biomolecule.